Limits and constitutional problems of the “harmonising” Wealth Tax in Spain (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2022)
The approval of the “Temporary Solidarity Tax on Wealth”, as a sort of “complementary” tax to the existing Wealth Tax, raises doubts about its compatibility with the financial autonomy of the Autonomous Communities and, more specifically, with the framework of tax devolution itself. At the same time, it departs from the proposals for reform of this type of taxation, both international and derived from national reports, such as the White Paper on Tax Reform.The purpose of this article is to examine some of the questions raised by the creation of this curious tax figure, examining the appropriateness of establishing the ITSGF in the context of wealth taxation and in the light of both the international context and the recommendations of the studies and reports that have examined this type of taxation. An assessment is made of the new tax, based on its central elements, verifying its relationship with the exercise of the Autonomous Communities’ regulatory powers, as well as its suitability for fulfilling the purposes for which it was introduced into the tax system. Finally, the reform will be contrasted with the current legal framework for the transfer of taxes, with emphasis on the evolution of the transfer of the IP itself, and with the aim of reaching an initial conclusion on the effect that the establishment of the ITSGF implies, as well as the existing alternatives to the option followed by the legislator.
Keywords: Taxation; solidarity; patrimony; fiscal federalism; co-ordination